$G_{δ σ }$ GAMES AND INDUCTION ON REALS. (13th December 2021) - AGUILERA, J. P.; WELCH, P. D.
Abstract: It is shown that the determinacy of $G_{δ σ }$ games of length $ω ^2$ is equivalent to the existence of a transitive model of ${\mathsf {KP}} + {\mathsf {AD}} + Π _1-MI_{\mathbb {R}}$ containing $\mathbb {R}$ . Here, $Π _1-MI_{\mathbb {R}}$ is the axiom asserting that every monotone $Π _1$ operator on the real numbers has an inductive fixpoint.